Pengaruh Ukuran Perusahaan dan Struktur Modal terhadap Nilai Perusahaan pada Perusahaan Perbankan yang Tercatat di BEI Periode Tahun 2020-2024 - Shafira, Rinda; Elmira Siska (EBISMAN eBisnis Manajemen, 2026)
Investors consider firm value as an indicator of a company’s success and its future prospects. Several financial variables, such as firm size and capital structure, are believed to influence firm value in the banking industry. Financial institutions with large total assets are often perceived as more stable and less vulnerable to risk, thereby increasing investor confidence. In addition, capital structure, commonly measured by the Debt to Equity Ratio (DER), plays an important role in evaluating a company’s financial performance and its impact on firm value. This study aims to examine the effect of firm size and capital structure on firm value in banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The research employs a quantitative approach using multiple linear regression analysis. Secondary data were obtained from financial statements and stock price information published on the official IDX website. The sample consists of 12 BUKU 2 banking companies selected through purposive sampling, with an observation period of five years. Firm size is measured using the natural logarithm of total assets (Ln Total Assets), capital structure is proxied by the Debt to Equity Ratio (DER), and firm value is measured using Price to Book Value (PBV). The results indicate that, simultaneously, firm size and capital structure have a significant effect on firm value.